STRATEGI PEMASARAN DIGITAL UNTUK MENINGKATKAN PENJUALAN UMKM DI INDONESIA - sari, Junida; Putri, Juliana (Program Studi Perbankan Syariah, Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh, 2024)
Digital marketing has become a key factor in business success, including for Micro, Small and Medium Enterprises (MSMEs) in Indonesia. Along with technological developments and increasingly high internet penetration, MSMEs need to adopt digital marketing strategies to increase their competitiveness and sales. This research aims to analyze effective digital marketing strategies for MSMEs in Indonesia to increase sales and expand the market. The method used in this research is a literature study and qualitative analysis of the implementation of digital marketing in several MSMEs in Indonesia. The research results show that digital marketing strategies that can increase MSME sales include the use of social media, content-based marketing, digital advertising, and optimizing e-commerce platforms. Apart from that, the importance of improving digital skills for MSME players and strengthening connections between MSMEs and consumers through digital platforms is a determining factor for success. By implementing the right digital marketing strategy, MSMEs in Indonesia can expand market reach, increase visibility, and ultimately drive significant sales growth. It is hoped that this research can provide insight for MSME players and stakeholders to further optimize digital marketing potential in facing increasingly competitive market challenges.